Pemanfaatan Ekstrak Tanaman Ciplukan (Physalis Angulat L.) sebagai Terapi Anemia pada Remaja di Masa Menstruasi: Utilization of Ciplukan Plant Extract (Physalis Angulat L.) as a Therapy for Anemia in Adolescents during Menstruation - Emi Yunita; Sari Pratiwi Apidianti (Universitas Muhammadiyah Sidoarjo, 2019)
Anemia is often associated with conditions of weakness, fatigue, lethargy due to lack of iron in the blood. Not only in adults, children and even toddlers can be affected by anemia. A survey shows that anemia is higher affected to women than men. If anemia occurs in a girl, the effect is not only on the child but also to the next generation. This research is an experimental analytic research, a study based on the level of neutrality place of research to survey research and naturalistic (qualitative). In essence, the experimental research is examining the effect of treatment on behavior that arises as a result of treatment. This study aims to determine the use of Ciplukan extract to increase the iron in the blood, whether it has influences to the increase in hemoglobin levels, so that it can be used as a therapy for anemia That has experienced by adolescence during menstruasion. In addition, the study also obtained information on how to reduce the intensity of menstrual pain by using non-pharmacological techniques, namely by consuming of Ciplukan extract.